The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/asi1030021
|View full text |Cite
|
Sign up to set email alerts
|

Spinning Reserve Capacity Optimization of a Power System When Considering Wind Speed Correlation

Abstract: Usually, the optimal spinning reserve is studied by considering the balance between the economy and reliability of a power system. However, the uncertainties from the errors of load and wind power output forecasting have seldom been considered. In this paper, the optimal spinning reserve capacity of a power grid considering the wind speed correlation is investigated by Nataf transformation. According to the cost-benefit analysis method, the objective function for describing the optimal spinning reserve capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Operating reserve planning accounting for probabilistic factors can be traced back to 1963 [2], and since that period, the literature has documented several operating reserve planning schemes to economically hedging against outage risk, especially for renewable energy systems in recent passing years [3–8]. Profiting from the rapid development of advanced computation techniques and equipment, contemporary power systems can be safeguarded with operating reserve of coordinated response abilities against a broad spectrum of contingencies, that is precisely why hazardous blackout has been compressed to be much rare.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Operating reserve planning accounting for probabilistic factors can be traced back to 1963 [2], and since that period, the literature has documented several operating reserve planning schemes to economically hedging against outage risk, especially for renewable energy systems in recent passing years [3–8]. Profiting from the rapid development of advanced computation techniques and equipment, contemporary power systems can be safeguarded with operating reserve of coordinated response abilities against a broad spectrum of contingencies, that is precisely why hazardous blackout has been compressed to be much rare.…”
Section: Introductionmentioning
confidence: 99%
“…Operating reserve planning accounting for probabilistic factors can be traced back to 1963 [2], and since that period, the literature has documented several operating reserve planning schemes to economically hedging against outage risk, especially for renewable energy systems in recent passing years [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reference [10] found that system generation capacity may be influenced by multipliers related to the risk of overestimation as well as the cost of underestimating the available wind power. Moreover, the optimal spinning reserve cost of a wind power system can be used to evaluate the influence of wind power on the selection of the spinning reserve level of a power system [11], [12]. Reference [13], [14] found that as the wind power capacity increased, the system increased the amount of reserve carried or faced a measurable decrease in reliability.…”
Section: Introductionmentioning
confidence: 99%